Typology of International Obligations - Hassan Savari; Mohammad Saleh Attar (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2015)
The UN charter as the foremost instrument in giving birth to International contemporary order- has laid the foundation of a new regime which is deemed by many as a revolution against Westphalia order of International law. This profound evolution is chiefly based on introduction of sociological premises as the main guide line in framing the International order. Learning lessons from its short lived inchoate predecessor – The Covenant of the League of Nations 1919 – the new regime along with structural concepts, resorts to globalized normative sociological norms in its attempt to frame the new order. In realization of its set targets however, the system suffers a quite number of deficiencies; that is there exist norms and structures in the system that may adversely affect its desired goals. Nonetheless, the introduction of the new order under the auspices of the principles and the  perspectives are set forth in the charter requires appropriate legal mechanisms in order to open door to realization of  legal universalism era – a step forward towards further development of reciprocal  order  - a target desired while formulation of the charter was underway. Emerging of new International commitments serve as prominent legal tools to regulate and arrange the new order. Such rights and duties, which take various forms and consequence, are governed by corresponding legal regimes. These regimes, which have roots in their predecessors and any future generation of regime will be emerged, shall evolve based on the needs, requirements and developments that may arise time to time.  This paper aims at studying International obligations and their corresponding legal regimes with regards to their existing status in International interactions.